Nordic writings or fragmentation through exile and the madness of female characters in Mohammed Dib - BOUCHENE, Karima (Journal of Human Sciences, 2020)
In this work we try to highlight the notion of binarism and duplication present in the trilogy Nordic Mohamed Dib the objective of this analysis is to dissect this notion and analyze it in its context diegetic, and see how much the strands of our corpus interact with each other as chapters, constituting a work and not novels that constitute a trilogy, or even a quadrilogy, we will base ourselves on transfiction as an approach, especially the works of Saint Gelais, and the psychocritic of Charles Mauron and Philippe Hamon in the semiological analysis of character especially those who are split; to discover that all male and female characters in the entire trilogy are just one fragmented and split character to seek and to identify with a specific nation and also to appropriate an identity lost because of the exile.